Convalescent plasma therapy in COVID-19 - Uysal, Ayse; Erkurt, Mehmet Alı; Kuku, Irfan; Sarıcı, Ahmet; Biçim, Soykan; Kaya, Emin; Berber, Ilhami (My University, 2022)
The coronavirus disease 2019 (COVID?19) affected many people in a short time and 5-10% of them were severely affected by the disease. A variety of treatment methods\rhave been developed for this rapidly spreading disease and vaccine studies have been initiated. One of these treatment methods is convalescent plasma (CP) therapy which\ris a passive immunization therapy. CP method is based on the principle of giving the plasma containing the antibodies formed against the pathogen to people who have\ractive disease after they have recovered from the disease which is a very effective but short-term solution until a definitive and permanent treatment (vaccine, drug, etc.)\ris found in pandemic conditions. Here, we presented the use of CP in the COVID-19 pandemic.
Keywords: Genel ve Dahili Tıp; Mikrobiyoloji